Primer Design of Volatile Synthesis Coding Genes in Ralstonia syzygii subsp. celebesensis - Damanik, Nina Septania; Prakoso, Ady Bayu; Triyana, Kuwat; Subandiyah, Siti (Universitas Gadjah Mada, 2023)
Microbes produce various types of volatile organic compounds (VOCs) through metabolism, which can be used for diagnostic purposes. Microbes' types and classes of VOCs are very wide, including fatty acid derivatives (hydrocarbons, alcohols, and ketones), aromatic compounds, nitrogen-containing compounds, and volatile sulfur compounds. Microbial volatile organic compounds (VOCs) can also be divided into several chemical classes: alkenes, alcohols, ketones, benzos, pyrazines, sulfides, acids, esters, and terpenes. This study aimed to design primers for genes encoding volatile synthesis in Ralstonia syzygii subsp. celebesensis, which causes blood disease in the banana plant. Some of the genes involved are adc (acetone synthesis), adhP (ethanol synthesis), ilvA, nirBD (ammonia synthesis), mdcA (propionic acid synthesis), cysI (hydrogen sulfide synthesis), and speBC (putrescine synthesis). Primers were designed and examined for specificity in silico using Primer3Plus, Geneious Prime, and BLAST programs. The numbers of nine pairs designed primers were successfully amplifying the related nine VOC genes of R. syzygii subsp. celebesensis for qPCR.